Two-stage wrinkling of Al films deposited on polymer substrates. (15th March 2019) - Wu, K.; Yuan, H.Z.; Li, S.J.; Zhang, J.Y.; Liu, G.; Sun, J.
Abstract: This study reveals two-stage wrinkling behavior of Al films deposited on polydimethylsiloxane (PDMS) substrates by magnetron sputtering at a high temperature. The hierarchical structures with nano-micro dual scale wrinkles were created in Al films. The micro-scale wrinkles originated from thermal contraction, with the wavelength increasing with increasing film thickness, while nano-scale wrinkles, with an almost unchanged wavelength, are induced by the expansion of the mixed layer on the PDMS surface. The results provide a facile method to produce the hierarchical wrinkled surfaces for functionality. Graphical abstract: Unlabelled Image